Refractory fulminant colitis following ocrelizumab therapy requiring colectomy in a patient with multiple sclerosis. Issue 12 (14th December 2022) - Malloy, Reuben; Fernandes, Richard; Begun, Jakob; An, Yoon-Kyo
Abstract : A woman in her 40s was referred for acute and chronic postprandial abdominal cramps on a background of relapsing remitting multiple sclerosis on ocrelizumab therapy as well as coeliac disease on a gluten-free diet, with a family history of ulcerative colitis. Initial colonoscopy demonstrated mild patchy colitis. The patient was trialled on mesalazine, which was ceased due to intolerance. Subsequently, she continued on mercaptopurine monotherapy for management of mild symptoms. Despite this, her symptoms rapidly progressed, with endoscopic and histological evidence of severe rectal-sparing pancolonic inflammation, consistent with severe ocrelizumab-induced colitis. This was refractory to intravenous methylprednisolone and intravenous cyclosporine rescue therapy, requiring surgical management with a subtotal colectomy and subsequent ileorectal anastomosis, after which she remained in clinical, endoscopic and histological remission.